Pengaturan Sistem Dan Mekanisme E-Voting Dalam Pemilihan Kepala Desa - Syukur, Yohanes Paulus; Ratu Udju, Hernimus; Benu, Yonas S O (Artemis Law Journal, 2025)
The electronic voting system in village head elections is a breakthrough in digital democracy that aims to increase transparency and efficiency. This study focuses on a legal review of e-voting based on Village Law No. 6/2014 and the Constitutional Court's decision, which allows the use of this method as long as the principles of democratic elections are followed. The e-voting process involving e-KTP can reduce the possibility of fraud, speed up the vote counting process, and reduce logistics costs. Some of the challenges faced include infrastructure readiness, digital literacy levels, and human resource capabilities. Implementation in various regions since 2013 has shown that this method can be applied, although a gradual approach is needed. In conclusion, e-voting has the potential to change the democratic system in villages if supported by appropriate regulations, capacity building, and socialization that embraces all parties.